Law No. 61 of the Year 2016 on Extending the Period of the Trade Union Term and Amending Some Provisions of Law No. 35 of the Year 1976 on Issuing the Trade Unions Law = قانون رقم 61 لسنة 2016 بمد مدة الدورة النقابية وتعديل بعض أحكام القانون رقم 35 لسنة 1976 بإصدار قانون النقابات العمالية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic